Pendampingan Belajar Kosa Kata Bahasa Arab dengan Metode Audio Visual di TK/TPA Al Fathani Gowa - Agusriani, Ade; Sri Mulya; Aydil Hisyaf; Dian Chaerani; Jami'atul Khaerah (Faculty of Tarbiyah and Teacher Training, 2025)
Vocabulary acquisition in early childhood requires methods suited to children's cognitive and developmental characteristics. This community service project aimed to assist Arabic vocabulary (mufrodat) learning through the audio-visual method at TK/TPA Al-Fathani, Gowa. The implementation stages included planning, which covered material development, instructional techniques, assignment of session responsibilities, and preparation of learning tools. The content focused on numbers 1–10, emphasizing meaning accuracy, pronunciation, vocabulary mastery, and sequencing. The teaching process utilized songs, videos, flashcards, and direct practice. Grounded in behaviorist and cognitivist theories, this approach aimed to build language habits and understanding through engaging, multisensory experiences. Results showed that the audio-visual method created an enjoyable learning atmosphere, increased children’s active participation, and effectively supported their memorization of Arabic numbers.